The evolution of price discrimination in the European car market - PinelopiKoujianou Goldberg; Frank Verboven (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1999)
Car prices in Europe are characterized by large and persistent differences across countries. The purpose of this paper is to document and explain this price dispersion. Using a panel data set extending from 1980 to 1993, we first demonstrate two main facts concerning car prices in Europe: (1) The existence of significant differences in quality adjusted prices across countries, with Italy and the U. K. systematically representing the most expensive markets. (2) Substantial year-to-year volatility that is to a large extent accounted for by exchange rate fluctuations and the incomplete response of local currency prices to these fluctuations. These facts are analyzed within the framework of a multiproduct oligopoly model with product differentiation. The model identifies three potential sources for the international price differences: price elasticities generating differences in markups, costs, and import quota constraints. Local currency price stability can be attributed either to the presence of a local component in marginal costs, or to markup adjustment that is correlated with exchange rate volatility; the latter requires that the perceived elasticity of demand is increasing in price. We find that the primary reason for the higher prices in Italy is the existence of a strong bias for domestic brands that generates high markups for the domestic firm (Fiat). In the U. K. higher prices are mainly attributed to better equipped cars and/or differences in the dealer discount practices. The import quota constraints are found to have a significant impact on Japanese car prices in Italy, France and the U. K.. With respect to local currency price stability, 2/3 of the documented price inertia are attributed to local costs, and 1/3 to markup adjustment that is indicative of price discrimination. Based on these results we conjecture that the EMU will substantially reduce the year-to-year volatility observed in the car price data, but without further measures to increase European integration, it will not completely eliminate existing cross-country price differences. – – Die Autopreise in Europa sind durch große und beständige Unterschiede zwischen Ländern gekennzeichnet. Ziel dieses Beitrages ist es, diese Preisstreuung zu erklären. Anhand eines Paneldatensatzes für den Zeitraum von 1980 bis 1993 wird erstens aufgezeigt, daß signifikante Unterschiede in qualitätsangepaßten Peisen zwischen den Ländern bestehen, wobei Italien und Großbritannien die teuersten Märkte aufweisen. Zweitens lassen sich beträchtliche Schwankungen von Jahr zu Jahr feststellen, die vor allem auf Wechselkursveränderungen und unvollständige Reaktionen bei der lokalen Preissetzung zurückzuführen sind. Diese Sachverhalte werden im Rahmen eines Mehrprodukt- Oligopol-Modells mit Produktdifferenzierung analysiert. Das Modell identifiziert drei potentielle Quellen für internationale Preisunterschiede: Preiselastizitäten, die unterschiedliche Gewinnspannen erzeugen, Kosten- und Importquotenbeschränkungen. Inwieweit diese Ursachen im einzelnen zutreffen, wird für die verschiedenen Länder ausführlich erörtert. Insgesamt lassen die Ergebnisse darauf schließen, daß sich im Gefolge der europäischen Währungsunion die von Jahr zu Jahr zu beobachtenden Schwankungen der Automobilpreise verringern dürften; sie verdeutlichen aber auch, daß ohne weitere Maßnahmen in Richtung europäische Integration die existierenden Preisunterschiede zwischen den einzelnen Ländern nicht vollständig verschwinden werden.
Keywords: 330